GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 6 species occurrences available in GBIF matching the query: TaxonKey: Pitcairnia anomala Hoehne. The dataset includes 6 records from 3 constituent datasets: 3 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 2 records from R-Tipos - Herbário do Museu Nacional - Tipos. 1 records from R - Herbário do Museu Nacional.
Keywords: GBIF; biodiversity; species occurrences